Percepções de indivíduos com sintomatologia psicopatológica e comportamento suicida sobre os impactos da pandemia em sua vida - Schott, Fabiane (2022)
In February 2020, Brazil was affected by the COVID-19 pandemic. With the aggravation of the disease, containment measures were implemented, which included social distancing and isolation. As a result, the effects of the pandemic on the mental health of the population were profound and could become even worse. There were studies linking depression and other serious psychopathologies with suicide in several cases during the pandemic, and there were suggestions that suicide rates would increase, and become an imminent concern as the pandemic spreads and its effects would be felt by the population. Therefore, the objective of this study was to understand the impacts of the pandemic on the perception of subjects with severe psychopathological symptoms and suicidal behavior. This is an exploratory, descriptive and qualitative study. The inclusion criteria were: Being over 18 years of age, presenting a clinical diagnosis for depression, affective mood disorder, schizophrenia, mixed anxiety and depressive disorder, and suicidal behavior. The exclusion criterion used consisted of presenting psychic fragility to respond to the interview. Twelve people participated, of both sexes, from Agudo, RS. The study took place through a semistructured interview held in December 2021. The results found showed greater damage to mental health and risk of life in four participants, compared to the others. The associated factors in these cases were related to the individual history, and the sum of others generated by the pandemic, such as isolation, distancing, changes in roles, and mainly due to the interruption of psychological and psychiatric treatments. Finally, as a prevention strategy, a booklet of recommendations for health professionals was prepared, containing information about the aggravation of risks identified in patients who interrupted mental health treatment. It was also suggested that the municipality create an instrument to monitor these serious cases in psychological distress and suicidal behavior, triggered by the pandemic.